Experimental O‐space turbo spin echo imaging. Issue 4 (15th May 2015) - Wang, Haifeng; Tam, Leo; Kopanoglu, Emre; Peters, Dana C.; Constable, R. Todd; Galiana, Gigi
Abstract : Purpose: Turbo spin echo (TSE) imaging reduces imaging time by acquiring multiple echoes per repetition (TR), requiring fewer TRs. O‐space can also require fewer TRs by using a combination of nonlinear magnetic gradient fields and surface coil arrays. Although to date, O‐space has only been demonstrated for gradient echo imaging, it is valuable to combine these two techniques. However, collecting multiple O‐space echoes per TR is difficult because of the different local k‐space trajectories and variable T2‐weighting. Theory and Methods: A practical scheme is demonstrated to combine the benefits of TSE and O‐space for highly accelerated T2‐weighted images. The scheme uses a modified acquisition order and filtered projection reconstruction to reduce artifacts caused by T2 decay, while retaining T2 contrast that corresponds to a specific echo time. Results: The experiments revealed that the proposed method can produce highly accelerated T2‐weighted images. Moreover, the method can generate multiple images with different T2 contrasts from a single dataset. Conclusions: The proposed O‐space TSE imaging method requires fewer echoes than conventional TSE and fewer repetitions than conventional O‐space imaging. It retains resilience to undersampling, clearly outperforming Cartesian SENSE at high levels of undersampling, and can generate undistorted images with a range of T2 contrast from a single acquired dataset.Magn Reson Med 75:1654–1661, 2016. © 2015 Wiley Periodicals, Inc.